“Why Care Now” in Forced Migration Research? Imagining a Radical Feminist Ethics of Care - Clark-Kazak, Christina (ACME, 2023)
This article lays out the ethical, epistemological, and methodological reasons for radical care ethics in research in forced migration. Drawing on a growing body of literature and recent initiatives to codify ethics in forced migration studies, it highlights the transformational potential of a radical feminist care approach to the “ethical turn” in the field. I suggest that radical care ethics re-centers reciprocal human relationships in forced migration research to address specific ethical challenges posed by the criminalization of migration, extreme power asymmetries, precarities in migration status and politicization of migration policies. It is incumbent on all forced migration researchers to think proactively and carefully about ethics beyond procedures prescribed by institutional processes. I conclude with ways in which we can build on examples of radical care ethics in forced migration studies to imagine an “otherwise” (Povinelli 2012b) in our field.